HLA-G Expression Is an Independent Predictor for Improved Survival in High Grade Ovarian Carcinomas. (27th May 2014) - Rutten, M. J.; Dijk, F.; Savci-Heijink, C. D.; Buist, M. R.; Kenter, G. G.; Vijver, M. J. van de; Jordanova, E. S.
Abstract : Aberrant expression of human leukocyte antigens (HLA) class I has prognostic importance in various cancers. Here, we evaluated the prognostic value of classical (A/B/C) and nonclassical (G/E) HLA expression in 169 high grade epithelial ovarian cancer samples and linked that to clinicopathological characteristics and survival. Expression of HLA-A, -B/C, or -E was not correlated with survival. Survival was prolonged when tumours expressed HLA-G ( P = 0.008 ) and HLA-G was an independent predictor for better survival ( P = 0.011 ) . In addition, HLA-G expression was associated with longer progression-free survival ( P = 0.036 ) and response to chemotherapy ( P = 0.014 ) . Accordingly, high expression of HLA-G mRNA was associated with prolonged disease-free survival ( P = 0.037 ) in 65 corresponding samples. Elevated serum-soluble HLA-G levels as measured by enzyme-linked immunosorbent assay in 50 matched patients were not correlated to HLA-G protein expression or gene expression nor with survival. During treatment, sHLA-G levels declined ( P = 0.038 ) . In conclusion, expression of HLA-G is an independent prognostic factor for improved survival in high grade epithelial ovarian cancer and a predictor for platinum sensitivity.